2017
DOI: 10.1080/14767058.2017.1342806
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and maternal risk of breast cancer: a meta-analysis of cohort studies

Abstract: Current evidence did not support a conclusive association between PE, PIH and the maternal risk of breast cancer. Gender of the offspring may influence the association between PE and maternal breast cancer incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Despite this, research has produced conflicting results. Three meta-analyses have shown no association or inconclusive results [ 4 , 14 , 15 ] with similar findings reported in large primary studies [ 16 , 17 , 18 , 19 ]. In contrast, two cohorts and a case-control study showed increased cancer risk [ 20 , 21 , 22 ].…”
Section: Introductionsupporting
confidence: 63%
“…Despite this, research has produced conflicting results. Three meta-analyses have shown no association or inconclusive results [ 4 , 14 , 15 ] with similar findings reported in large primary studies [ 16 , 17 , 18 , 19 ]. In contrast, two cohorts and a case-control study showed increased cancer risk [ 20 , 21 , 22 ].…”
Section: Introductionsupporting
confidence: 63%
“…In this large registry‐linked pooled study based on data from four Nordic countries, women with a history of preeclampsia had an ∼10% reduced risk of breast cancer compared with women without this history. A recent meta‐analysis of preeclampsia and breast cancer yielded a relative risk (RR) of 0.87 (95% CI 0.80–0.94) based on prospective studies, but results from historical cohort studies showed significant heterogeneity and a lack of association (RR 0.97; 95% CI 0.79–1.18). This study indicated that other maternal, perinatal and neonatal characteristics, such as twin pregnancies, lower maternal BMI and premature delivery also were associated with elevated breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, prospective cohort studies have shown that preeclampsia, a pregnancy complication involving hypertension and proteinuria, is associated with a 10–20% decrease in maternal breast cancer risk . Gestational hypertension also has been associated with reduced risk, although less consistently.…”
mentioning
confidence: 99%
“…All Sister Study participants had a sister diagnosed with breast cancer, which may occur less frequently following preeclampsia, although the overall evidence is controversial . Still, sisters of women with breast cancer may have a lower risk of preeclampsia, possibly due to inherited factors .…”
Section: Commentmentioning
confidence: 99%
“…All Sister Study participants had a sister diagnosed with breast cancer, which may occur less frequently following preeclampsia, although the overall evidence is controversial. 6,41,42 Still, sisters of women with breast cancer may have a lower risk of preeclampsia, possibly due to inherited factors. 43 Thus, we cannot rule out that Sister Study participants may differ in terms of preeclampsia risk (and, possibly, risk factors) from the general population.…”
Section: Limitations Of the Datamentioning
confidence: 99%